Constructing Pedagogical Identity Through Local Culture-Based English Materials among Pre-Service Mathematics Teachers - Maria Ulpah; Muflihah Muflihah; Yusiana Rahman; Anam Fauzi (MASI Mandiri Edukasi, 2026)
In mathematics teacher education, English learning is often treated primarily as a linguistic requirement rather than as a pedagogically meaningful component of professional preparation. Consequently, English courses frequently contribute little to the development of pedagogical identity among pre-service mathematics teachers. This study aims to examine how local culture–based English learning materials function as a pedagogical space for the construction of pedagogical identity among pre-service mathematics teachers. This research employed a qualitative descriptive approach conducted in an English for Mathematics Learning course involving 80 sixth-semester pre-service mathematics teachers. Data were collected through open-ended questionnaires, classroom observations, and students’ written reflections embedded in culturally contextualized learning activities, and were analyzed using thematic analysis. The findings reveal that integrating local culture into English learning materials supports pedagogical identity development by encouraging culturally situated learning, reframing English as a pedagogical tool for explaining mathematical concepts, strengthening pedagogical confidence, and promoting reflective and collaborative learning practices. Cultural familiarity also reduces linguistic anxiety and enables students to position themselves more confidently as future mathematics teachers. These findings highlight the role of local culture as an epistemic and affective resource that supports participation, strengthens instructional confidence, and facilitates the development of pedagogical identity within mathematics teacher education.